Complex terrorist threats : Singapore's response - Joseph Franco (2015)
Recent terrorist incidents highlight the widening spectrum of potential targets and attack mehods by violent extremists. The increasing complexity of threats must be met with comprehensive initiaves which emphasise combined deterrence from governments and communities.